Finn Family Moomintroll - "Jansson, Tove" (Puffin Books: London, 2009)
It is spring in the Valley of the Moomins. And Moomintroll and his friends Snufkin and Sniff make an exciting discovery of a hat with magical powers. They have many adventures until the hat produces something unexpected inside the Moomin household that makes everyone wonder if perhaps the magic is more trouble than it's worth
Keywords: Fantasy & magical stories